The effect of the use of hand-held calculators on mathematics achievement and attitudes toward mathematics of freshman college students - De La Rosa, Fe G. (Animo Repository, 1990)
This study determines the effects of the use of hand-held calculators on the mathematics achievement and attitudes towards mathematics of freshman college students. The study was conducted among two of the sixteen intact mathematics of investment classes at DLSU. The two classes were assigned at random into the control and the experimental groups. The experimental group used hand-held calculators while the control group used the mathematical tables during the lessons on concept development. The researcher taught both classes the same content for 7 weeks. Both groups were given pre and post achievement tests and pre and post experimental attitude scales to determine and compare possible changes in their mathematics achievement and attitudes toward mathematics as a result of the experiment. The achievement test and the attitude scales were developed and validated by the researcher prior to actual use. The T-test for Dependent Samples and Analysis of Covariance with pre-achievement scores, college entrance math scores, reading comprehension scores, and academic potential index as covariates were used to verify the hypotheses of the study at the 0.05 level of significance. The use of hand-held calculators had a significant effect on the students' achievement based on the achievement test scores. This result was obtained after partialing out initial differences due to the four covariates. On the other hand, the use of hand-held calculators had no significant effect on the subjects' attitudes towards mathematics. There was no significant difference between the experimental and the control groups in terms of their attitudes towards the course. Based on the findings of the study, it can be concluded that the use of the hand-held calculator is more effective than the use of the mathematical tables in the development of concepts in a mathematics of investment course. It can also be concluded that the use of the hand-held calculator has no significant effect on the attitudes of students toward mathematics.